3b-4=5b-2

Simple and best practice solution for 3b-4=5b-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b-4=5b-2 equation:


Simplifying
3b + -4 = 5b + -2

Reorder the terms:
-4 + 3b = 5b + -2

Reorder the terms:
-4 + 3b = -2 + 5b

Solving
-4 + 3b = -2 + 5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-5b' to each side of the equation.
-4 + 3b + -5b = -2 + 5b + -5b

Combine like terms: 3b + -5b = -2b
-4 + -2b = -2 + 5b + -5b

Combine like terms: 5b + -5b = 0
-4 + -2b = -2 + 0
-4 + -2b = -2

Add '4' to each side of the equation.
-4 + 4 + -2b = -2 + 4

Combine like terms: -4 + 4 = 0
0 + -2b = -2 + 4
-2b = -2 + 4

Combine like terms: -2 + 4 = 2
-2b = 2

Divide each side by '-2'.
b = -1

Simplifying
b = -1

See similar equations:

| 9-5n=30 | | 4(b-2)=2(b-6) | | 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 | | 6y-2=14y+62 | | 7x+9=-29 | | 9=x-3 | | 6y-2=14y+64 | | 3h+1=3(h+1) | | 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 | | -6x-1=-1 | | 3(x-5)=6(x-6) | | 14x+23=-93 | | 7x+3(4x-1)=49 | | 12-8x-6=-13x+21 | | -3x-10=-10 | | 2x-4+x=8 | | (4x-7)-(2x-2)= | | -7x+5=-58 | | 64=8r+2 | | 7h=9.1 | | (2x+5x)=20 | | 6n-10=4n-2 | | 7x+2=4x+15 | | (49y)-2m=180 | | 3(x+2)=2(2x+5) | | 60+n+6=75 |

Equations solver categories